Evaluación del costo de servicio y su incidencia en la Rentabilidad del Hotel Nilas S.A.C. de la ciudad de Tarapoto, periodo 2013. - López Falcón, Gilber (2015)
This research, which is entitled "EVALUATION OF THE COST OF SERVICES AND ITS IMPACT ON PROFITABILITY OF HOTEL NILAS S.A.C. Tarapoto, 2013". Where Determine overall objective raised the cost of service and establish their impact on the profitability of Nilas Hotel in the city of Tarapoto, Period 2013. As the study shows 14 workers Nilas Hotel. Reached the following conclusions: effective control of manufacturing overhead is not carried, as they are recorded through loose and loose-leaf whose information set forth is still generic, without specifying basic information such as the cost of these for each room. As regards Internet service provision, they are reported in single sheets through the issuance of internal vouchers which are not pre-numbered nor validated by management. Because of this inadequate control and distribution expenses the company does it is difficult to determine the unit cost and utility for each room; why the present work was developed, aimed at determining the cost of the service in accordance with 34 rooms available at Hotel Nilas. The company under study does not have a modernized system for your records and an appropriate distribution of costs, the empirical method, which has certain limitations or difficulties in making distributions accordingly for each room is used, only reports information generic, so that the return you get is not appropriate, it conforms to that reality. It is therefore relevant implementing a costing system service which will allow greater control of service operations and the valuation of the cost elements in reference to the time and expense used. Ie a technical and efficient management of company resources and the ability to make timely and accurate decisions cost, generating improved corporate governance and profitability.